Edited by Adrian Cunningham - Allison Hunter; Gillian Oliver; Shauna Hicks; Tim Sherratt; Rowena Loo; Danielle Wickman; Alison McCrindle; Anne-Marie Condé; Shadrack Katuu; Bruce Smith; Baiba Berzins; Michael Piggott; et al. (Archives & Manuscripts, 2010)
Michele F Pacifico and Thomas P Wilsted (eds), Archival and Special Collections Facilities: Guidelines for Archivists, Librarians, Architects, and Engineers, Chicago, Society of American Archivists, 2009. 204 pp. ISBN 1 931666 31 8.Pacific Regional Branch International Council on Archives (PARBICA), Recordkeeping for Good Governance Toolkit, PARBICA, 2007 (ongoing). Available at <http://www.parbica.org/Toolkit pages/ToolkitIntropage.htm>, accessed 18 March 2010.Melissa M Terras, Digital Images for the Information Professional, Aldershot, Ashgate, 2008. 258 pp. ISBN 978 0 7546 4860 4.Maryanne Dever, Sally Newman and Ann Vickery, The Intimate Archive: Journeys Through Private Papers, Canberra, National Library of Australia, 2009.198 pp. ISBN 978 0 642 27682 7.Mark Greengrass and Lorna Hughes (eds), The Virtual Representation of the Past, Farnham, Ashgate, 2008. xxvi + 226 pp. ISBN 978 0 7546 7288 3.Elizabeth Shepherd, Archives and archivists in 20th century England, Farnham, Ashgate, 2009. xiii + 245 pp. ISBN 978 0 7546 4785 0.The Arts Centre, Melbourne, Nick Cave: The Exhibition, the Arts Centre, Melbourne; Queensland Performing Arts Centre, Brisbane; WA Museum, Perth; and National Library of Australia, Canberra, 2007-09.Graham Matthews, Yvonne Smith and Gemma Knowles, Disaster Management in Archives Libraries and Museums, Farnham, Ashgate, 2009. xiv + 229 pp. ISBN 978 0 7546 7273 9.Paul Eggert, Securing the Past: Conservation in Art, Architecture and Literature, Cambridge University Press, 2009. 290 pp. ISBN 978 0 521 89808 9 (hardcover); ISBN 978 0 521 72591 0 (paperback).David O Stephens, Records Management: Making the Transition from Paper to Electronic, Lenexa, Kansas, ARMA International, 2007. xvii + 292 pp. ISBN 978 1 931786 29 4.The National Archives of the United Kingdom, Corporate Memory: A guide to managing business archives, London, The National Archives, 2009. 24 pp. Available at <http://www.nationalarchives.gov.uk/documents/ corporate-memory.pdf>, accessed 18 March 2010; and Managing Business Archives: Best Practice Online, available at <http://www. managingbusinessarchives.co.uk/>, accessed 18 March 2010.Randall C Jimerson, Archives Power: Memory, Accountability and Social Justice, Chicago, Society of American Archivists, 2009. 466 pp. ISBN 1 93166 630 X.John Ridener, From Polders to Postmodernism: A Concise History of Archival Theory, Duluth, Litwin Books, 2009. 208 pp. ISBN 978 0 9802004 5 4.Standards Australia, Handbook: Recordkeeping Compliance (HB 278- 2009), Sydney, Standards Australia, 2009. 82 pp. ISBN 0 7337 9141 7.Simon Flagg and Sebastian Gurciullo, Footprints: the journey of Lucy and Percy Pepper, Melbourne, National Archives of Australia and Public Record Office Victoria, 2008. xii + 132 pp. ISBN 978 1 9208 0761 0.Alana Garwood-Houng (ed.), Proceedings of the 5th International Indigenous Librarians Forum: Brisbane, Australia June 4-7, 2007, Canberra, Aboriginal and Torres Strait Islander Library, Information and Resource Network (ATSILIRN), 2007. 139 pp. ISBN 978 0 6465 0522 0. $20.00 + postage and handling. Available at <http://wwwl.aiatsis.gov.au/atsilirn/ home/index.html>, accessed 18 March 2010.